2020
DOI: 10.1111/jocn.15477
|View full text |Cite
|
Sign up to set email alerts
|

Exploring acute care nurses’ decision‐making in psychotropic PRN use in hospitalised people with dementia

Abstract: Aims and objectives To understand how acute care nurses make decisions about administering “as‐needed” (PRN) psychotropic medications to hospitalised people with dementia (PWD). Background Behavioural and psychological symptoms of dementia occur in approximately 75% of PWD admitted to acute care. Despite this, few studies provide insight into the use and prevalence of psychotropic use in acute care. Design A qualitative descriptive design was used to explore acute care nurses’ decision‐making about PRN psychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 68 publications
0
39
0
Order By: Relevance
“…The most frequent indications for psychotropic prescribing were depression in nine studies [ 50 , 51 , 55 , 56 , 60 , 62 , 73 , 74 , 82 ], sleeping disorders in seven [ 54–56 , 59 , 63 , 74 , 82 ] and anxiety in six [ 54–56 , 73 , 74 , 82 ]. In seven studies, psychotropic medication was used to manage behaviours and BPSD [ 49 , 53 , 57 , 63 , 65 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most frequent indications for psychotropic prescribing were depression in nine studies [ 50 , 51 , 55 , 56 , 60 , 62 , 73 , 74 , 82 ], sleeping disorders in seven [ 54–56 , 59 , 63 , 74 , 82 ] and anxiety in six [ 54–56 , 73 , 74 , 82 ]. In seven studies, psychotropic medication was used to manage behaviours and BPSD [ 49 , 53 , 57 , 63 , 65 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…A range of benefits of psychotropic medicines were identified by patients, family caregivers and healthcare professionals including enabling normal functioning of patients [ 55 , 56 ], allowing family caregivers and healthcare professionals to feel that they were doing something to help [ 51 , 74 ], treating sleep disorders [ 49 , 53 , 55 , 56 , 59 , 63 , 80 ], managing aggressive and agitated behaviour and maintaining health and safety [ 49 , 53 , 57 , 65 , 80 , 81 ]. Findings suggested that there was variation with medication class with antipsychotics being seen by healthcare professionals as a last resort, but benzodiazepines being prescribed more freely [ 59 ].…”
Section: Risk Benefit Assessmentmentioning
confidence: 99%
See 3 more Smart Citations